Being Wholesaled: An Investigation of Chinese International Students’ Higher Education Experiences - Su, Mengwei; Harrison, Laura M. (Journal of International Students, 2016)
Using academic capitalism as a theoretical foundation, this phenomenological study examined the new study abroad experiences of Chinese college students in six popular English-speaking study destination countries—the U.S., the U.K., Australia, Canada, the Netherlands, and Singapore. Qualitative data collected from 20 interviews indicate some hosting higher education institutions prioritize enrollment growth and neglect recruitment process and student development. Three main findings are 1) delegating recruitment to overseas agencies causes mismatches between host institutions and the Chinese students, 2) Chinese students having insufficient language skills are prone to have a dissatisfied study abroad experience, and 3) high density of student population from one country impedes Chinese students’ integration on campus. Implications for higher educational professionals, students, and faculty are presented.